Sunday

November 23, 2014

November 23, 2014

Posted by **muffy** on Saturday, September 12, 2009 at 1:32pm.

Solve the inequality:

(2x-3)(4x)+x^2=>(3x+4)^2

I did 2x-3*4x

9x^2-12x on the left side

on the right side:

9x^2+24x+16

I substracted everything on the right side over to the left and made it => zero

9x^2-12x-9x^2-24x-16=>0

-36x-16=>0

x=<4/-9

I'm not sure if this is right or if I made an error somewhere.

- Math -
**bobpursley**, Saturday, September 12, 2009 at 2:49pmit is correct.

- Math -
**muffy**, Saturday, September 12, 2009 at 2:54pmTHANKS!

**Answer this Question**

**Related Questions**

pre-calc Question on a previous question - On the question below, Bob Pursley ...

Math - I need to show that the right side equals the left side but I am having ...

Math - I need to show that the right side equals the left side but I am having a...

math - A=1/2h (b1 + b2) Solve for b1 A=1/2h (b1 + b2) Solve for b1 I assume this...

proof by mathematical induction - subject is PreCalulus. 2^(k+3) = and < (k+3...

chem again - One more question- how do I balance this half-reaction in terms of ...

MATH - i need help filling this out! 4x-10=32-3x 4x-10+____=32-3x+22 ____-10+...

Physics - A 60.9 kg climber is using a rope to cross between two peaks of a ...

Trig - Proving Identities: 2 columns (tan + cot)^2 = sec^2 + csc^2 I'm having ...

Algebra - I don't understand how to do this problems: Solve for the variable r, ...